Modelling interconnectedness of subsurface flow processes from a simple conceptual infiltration model (2009)
"The study determined subsurface flow processes of 92.3 ha catchment area in order to examine functional relationship among the surface and subsurface flow variables from the water balance components data. Days without rainfall had zero infiltration while peak values of infiltrated water corresponded with peak rainfall. However, the Crawford and Linsley infiltration model was deficient by its inability to distinguish between days of zero rainfall and days when rainfall was less than 1.0 mm. Interflow occurred continuously even when there was no rainfall. This was shown to be responsible for the stream flows on dry days. Hence, total subsurface flows, a combination of interflow and groundwater flow, had the two components contributing to stream flow on days with rainfall. On days without rainfall, the interflow component was the only contributor to subsurface flows."